BROWNIES “DISUKA” BERBASIS TEPUNG KACANG UNDIS, TEPUNG UBI UNGU, DAN KACANG HIJAU SEBAGAI ALTERNATIF PMT-P IBU HAMIL KEK - Isdiany, Nitta; Fauziyah, Roro Nur; Hapsari, Agustina Indri; Dwipayani, Ni Kadek Mahesa (Poltekkes Kemenkes Bandung, 2024)
The World Health Organisation (WHO) reported in 2017 that the prevalence of chronic energy deficiency (CED) among pregnant women worldwide ranged from 35-75%. According to the 2018 Riskesdas, the prevalence of CED among pregnant women in Indonesia was 17.3%, and the province of West Java was 14.1%. This prevalence is still above the target of the 2020-2024 Strategic Plan with target 10%. One of the intervention carried out is the provision of additional food. Alternative additional food can made independently or in groups by utilising various local foods in various forms like brownies. Brownies with the formulation of black mung bean flour and purple sweet potato flour can be used as an alternative high-energy high-protein additional food for pregnant women with CED. The purpose of this resarch is to determine the effect of black mung bean flour and purple sweet potato flour formulations on organoleptic, contain of protein, fat, carbohydrate, fibre and iron also the price of brownies. The research design is experimental and the sample in organoleptic testing is 35 moderately trained panellists. The results of the study on the organoleptic of the three formulas concluded that there was a significant difference with p (0.041) < α (0.05) in taste, and there was no difference in smell, colour, texture and overall with p > 0.05. F3 is the best formula that is favoured by the panellists. The results of the proximate test obtained nutrition values/100 grams brownies are 5.78 grams of protein, 15.03 grams of fat, 58.74 grams of carbohydrates, 15.30 grams of fibre and 1.6 mg of iron with the price of one serving (135 grams) is Rp.9,864.86. Recommendations for adding high-protein ingredients to increase the protein of the product.